Analisis Pengaruh Digital Marketing terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi: Studi pada Perusahaan Kosmetik yang terdaftar di Bursa Efek Indonesia - Nugrah Leksono Putri Handayani; Poppy Fitrijanti Soeparan; Mohammad Hidayatul Holili (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of digital marketing on firm value and to examine the mediating role of profitability. The research employs a quantitative approach with an explanatory research design. The sample consists of six cosmetic companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, selected using purposive sampling based on data availability. The analytical technique used is Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS) using SmartPLS 4. The study utilizes secondary data obtained from the companies’ annual financial reports. The results indicate that digital marketing has a positive and significant effect on firm value. Digital marketing also shows a positive effect on profitability; however, this effect is not statistically significant. Meanwhile, profitability has a positive and significant effect on firm value. The indirect effect test yields a coefficient (O) of 0.239, a t-statistic of 1.914, and a p-value of 0.056, indicating that profitability does not mediate the relationship between digital marketing and firm value. These findings suggest that digital marketing strategies have a more dominant direct effect on enhancing firm value than an indirect effect through profitability.